Effect of pre- and post-heading waterlogging on growth and grain yield of four millets. (2nd July 2016) - Matsuura, Asana; An, Ping; Murata, Kouhei; Inanaga, Shinobu
Abstract: Seeds of Panicum miliaceum, Panicum sumatrense, Setaria glauca, and Setaria italica were raised in polyvinylchloride tubes filled with soil to determine interspecific differences in waterlogging tolerance and the effect of pre- and post-heading waterlogging on growth and grain yield. Four treatments were conducted including control (no-waterlogging stress during growth). Pre-heading waterlogging treatment was initiated 17 days after sowing to heading (TC). Post-heading waterlogging treatment was initiated heading till harvest (CT). Waterlogging treatment was initiated 17 days after sowing to harvesting (TT). The grain yield of P. miliaceum, S. glauca, and S. italica decreased 16, 18, and 4%, while that of P. sumatrense increased 210% under TT treatment and this showed P. sumatrense had most waterlogging tolerance. The grain yield was more affected under TC treatment in S. italica and P. miliaceum. However, there was not significant differences the grain yield between TC and CT treatment in P. sumatrense and S. glauca . Total dry weight, total root dry weight, number of crown root, and the proportion of lysigenous aerenchyma of P. sumatrense were significantly higher than those of other millets at harvesting. Plant growth rate, total root dry weight, number of crown root, and the proportion of lysigenous aerenchyma of P. sumatrense were significantly higher than those of other millets at heading. These results suggest that P. sumatrense exhibits waterlogging tolerance by enhancing root growth characterized by a high proportion of lysigenous aerenchyma in the crown root.